Juvenile and small fish diversity in mangroves of different root types in the Labuhan Coastal Area, Bangkalan, Indonesia - FARID KAMAL MUZAKI; DIAN SAPTARINI; ACIB SETIA IBADAH (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Muzaki FK, Saptarini D, Ibadah AC. 2019. Juvenile and small fish diversity in mangroves of different root types in the Labuhan Coastal Area, Bangkalan, Indonesia. Biodiversitas 20: 1537-1543. The complexities of mangrove root types are well known to have effect on communities of fish including larval, juvenile and adult stages. This study aimed to access the difference on species composition and diversity of juvenile and small fish from mangrove area of different root types, especially in mangroves of the coastal area of Sepulu, Bangkalan which is a mangrove protection area. The samples were collected from November 2016 to June 2017 using modified centipede nets and scoop nets. Four types of sampling locations were used. Areas with pneumatophores (S), stilt roots (R), a combination of both types (C) and areas without mangroves (T). At least 32 species from 16 families of juvenile and small fish were identified. Families of fish with highest number of species were Gobiidae with 13 species, followed by Ambassidae, Mugilidae, Eleotridae and Siganidae with 2 species each. Fish species with highest abundance in all sampling sites and periods were Oryzias javanicus (F. Adrianichthyidae, 22.039%), Ambassis kopsii (F. Ambassidae, 17.878%), Liza vaigiensis (F. Mugilidae, 9.613%), Am. buruensis (F. Ambassidae, 9.261%), Terapon jarbua (F. Terapontidae, 7.562%), L. subviridis (F. Mugilidae, 7.385%) and Pseudogobius javanicus (F. Gobiidae, 7.385%), respectively. Result of two-way Anova (p=0.05) suggest that area with stilt roots (R) which were dominated by mangrove Rhizophora have relatively higher abundance and species richness of juvenile and adult small fish. In addition, average Shannon-Weaner diversity index (H’) value in areas with stilt roots was 2.031 and highest compared to the other sampling sites.